2013
DOI: 10.1007/s10711-013-9845-2
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of the moduli space of abelian differentials in genus 3

Abstract: The moduli space of curves endowed with a nonzero abelian differential admits a natural stratification according to the configuration of its zeroes. We give a description of these strata for genus 3 in terms of root system data. For each non-open stratum we obtain a presentation of its orbifold fundamental group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Remark 4.7. The symmetric mapping class group SMod(π * ) is an infinite-index subgroup of Mod(π * ) corresponding to the orbifold fundamental group 8 of projectivized hyperelliptic connected components of the moduli spaces of translation surfaces: see, e.g., Looijenga-Mondello [10]. Thus, we have just shown that, in a certain sense, the hyperelliptic Rauzy diagrams "see" the topology of the projectivized hyperelliptic connected components of the moduli spaces of translation surfaces.…”
Section: 22mentioning
confidence: 99%
“…Remark 4.7. The symmetric mapping class group SMod(π * ) is an infinite-index subgroup of Mod(π * ) corresponding to the orbifold fundamental group 8 of projectivized hyperelliptic connected components of the moduli spaces of translation surfaces: see, e.g., Looijenga-Mondello [10]. Thus, we have just shown that, in a certain sense, the hyperelliptic Rauzy diagrams "see" the topology of the projectivized hyperelliptic connected components of the moduli spaces of translation surfaces.…”
Section: 22mentioning
confidence: 99%
“…We stress that Theorem C is already non-optimal in genus 2, since PΩM ′ 2 (2) and PΩM ′ 2 (1, 1) are affine, and in genus 3, since PΩM ′ 3 (4) and PΩM ′ 3 (3, 1) are affine (see [25]). As an extension of Looijenga's question, it seems natural to wonder the following.…”
Section: 42mentioning
confidence: 99%
“…The conjecture says that each connected component of M d has homotopy type K(G, 1), where G is a group commensurable to some mapping class group. Hamenstädt uses the results in (Looijenga & Mondello, 2014)…”
Section: Introductionmentioning
confidence: 99%